Production of ciprofloxacin loaded chitosan/gelatin/bone ash wound dressing with improved mechanical properties - AYCAN, DİDEM; ALEMDAR YAYLA, NESLİHAN (ELSEVIER SCI LTD, 2019)
Polymeric films with enhanced mechanical performance were fabricated by incorporation of bone ash (BA) at various concentrations (0-25 v. %) into chitosan/gelatin (CTS/GEL) polymeric structure as a wound healing-dressing. The test results for mechanical performance of polymeric films proved that the encapsulation of BA into the polymeric films enhances the elastic modulus and tensile strength of polymeric films significantly. Oxygen permeability and water vapor transmission rate (WVTR) of films were also improved by BA reinforcement. Ciprofloxacin was chosen as the antibacterial model drug. The release of ciprofloxacin was provided in a more controlled manner at pH 7.4 owing to the incorporation of bone ash into the polymeric films. Also, drug loaded films showed great antibacterial activity against Escherichia coli and Bacillus subtilis bacteria. The results prove that ciprofloxacin loaded BA reinforced CTS/GEL composite films are potentially applicable in controlled drug delivery as wound dressings.
Keywords: Chitosan; Gelatin; Bone ash; Wound dressing; Mechanical performance; Ciprofloxacin; CROSS-LINKING; CHITOSAN SPONGES; BONE ASH; GELATIN; HYDROGEL; RELEASE; FILMS